2021
DOI: 10.5755/j01.ee.32.1.27382
|View full text |Cite
|
Sign up to set email alerts
|

Financial Distress Prediction for Small and Medium Enterprises Using Machine Learning Techniques

Abstract: Financial distress prediction is a key challenge every financing provider faces when determining borrower creditworthiness. Inherent opaqueness of Small and Medium Enterprise business complicates credit decision making process, therefore increasing cost to finance and lowering probability of receiving funds. This paper used data on 12.000 SMEs to estimate binomial classifiers for financial distress prediction using Logistic Regression, Artificial Neural Networks and Random Forest techniques. Classical financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 42 publications
2
18
0
1
Order By: Relevance
“…In general, our results show the superior performances of logistic regression over neural networks. These findings are in line with the works of Du Jardin and Séverin (2012), Islek and Oguducu ( 2017), Kim et al (2018), Lukason and Andresson (2019), and Malakauskas and Lakštutien ė ( 2021). For example, logistic regression reached for Du Jardin and Séverin (2012) an accuracy of 81.6% against 81.3% for neural networks with data collected over one year.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In general, our results show the superior performances of logistic regression over neural networks. These findings are in line with the works of Du Jardin and Séverin (2012), Islek and Oguducu ( 2017), Kim et al (2018), Lukason and Andresson (2019), and Malakauskas and Lakštutien ė ( 2021). For example, logistic regression reached for Du Jardin and Séverin (2012) an accuracy of 81.6% against 81.3% for neural networks with data collected over one year.…”
Section: Discussionsupporting
confidence: 89%
“…For neural networks, our best results outperform those of Kim et al (2018), Lukason and Andresson (2019), Papana and Spyridou (2020), and Malakauskas and Lakštutien ė (2021). For instance, using neural networks with 42 nodes in the hidden layer, Kim et al (2018) found an accuracy of 71.9% through 41 financial ratios selected from 1548 Korean heavy industry companies.…”
Section: Discussionmentioning
confidence: 88%
“…In terms of prediction methods, as summarized by Yazdanfar and Nilsson (2008) as well as Jackson & Wood (2013), the development of bankruptcy research can be classified into three stages: in the first stage, multiple discriminant analysis worked as the main statistical tool in late 1960s and 1970s after the research of Beaver (1966) and Altman (1968), which attempts to "classify the statistical units (objects) into two or more pre-defined groups" (Omelka et al, 2013(Omelka et al, , p. 2588; in the second stage, logit and probit models as the representative of conditional probability models have been developed by Ohlson (1980) and Zmijewski (1984) since 1980s ; in the third stage, with the development of computer technology, artificial neural networks as the representative method of data mining and machine learning techniques have started to be used in bankruptcy research since 1990s, which assume non-linearity of financial distress function (Malakauskas & Lakstutiene, 2021;Mselmi et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main involvement of this research is a significant development of the predictive accuracy in the short term (twelve months) by ML methods, related with the advanced when creating precise mid and long term predictions. Malakauskas et al [18] utilized data on 12.000 SMEs for estimating binomial classifications for financial distress prediction by LR, ANN, and RF methods. Traditional financial ratios have been utilized for estimating the early single period predictor that was improved using age factor, time, and credit history for retrieving multi period modules.…”
Section: Prior Fcp Models For Smesmentioning
confidence: 99%